2012
DOI: 10.1016/j.jpainsymman.2011.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Episodic (Breakthrough) Pain Prevalence in a Population of Cancer Pain Patients. Comparison of Clinical Diagnoses With the QUDEI—Italian Questionnaire for Intense Episodic Pain

Abstract: Because BP-EP is a significant phenomenon in cancer pain management, its appropriate recognition requires a more widely, internationally accepted general definition and specific validated tools for its screening and evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
1
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 21 publications
6
46
1
3
Order By: Relevance
“…In some studies, peaks of pain intensity have been reported independently on the analgesic treatment, and in others no clear distinction between background and BTcP pain intensity has been reported [10][11][12][13][14]16,17 . We have previously shown that many studies of BTcP have been performed in patients with uncontrolled background pain.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, peaks of pain intensity have been reported independently on the analgesic treatment, and in others no clear distinction between background and BTcP pain intensity has been reported [10][11][12][13][14]16,17 . We have previously shown that many studies of BTcP have been performed in patients with uncontrolled background pain.…”
Section: Discussionmentioning
confidence: 99%
“…Factors other than differences in symptom and disease burden might influence the reported prevalence. These factors include differences in definitions and diagnostic criteria (3,4), and inclusion of patients with poorly controlled background pain (5). …”
Section: Introductionmentioning
confidence: 99%
“…This approach has been largely used in patients' selection in most studies of BTcP. In some epidemiological studies, there was no operational definition a priori, even though patients could have their pain uncontrolled or were not receiving opioids [9,10]. For example, background pain intensity was severe-maximal in more than half of patients, and differently from what has been observed by others [9,11], surprisingly, the intensity of baseline pain was higher in patients without BTcP.…”
Section: Definition and Epidemiologymentioning
confidence: 99%
“…In some epidemiological studies, there was no operational definition a priori, even though patients could have their pain uncontrolled or were not receiving opioids [9,10]. For example, background pain intensity was severe-maximal in more than half of patients, and differently from what has been observed by others [9,11], surprisingly, the intensity of baseline pain was higher in patients without BTcP. In other studies, most patients had uncontrolled background pain, were receiving nonopioid analgesics or weak opioids, or were unsatisfied with their pain control [11,12].…”
Section: Definition and Epidemiologymentioning
confidence: 99%